PENINGKATAN EFEKTIVITAS WAKTU DAN KAPASITAS PRODUKSI JAMU TRADISIONAL DI TANJUNG DUREN GROGOL JAKARTA BARAT MELALUI PENGGUNAAN MESIN SERUT DAN SPINNER: - Sobron Yamin Lubis; Silvi A; Heru Budi Kusuma; Bryan Willynata; Muhammad Calvine Ferdinand; Salma Khaula Bazla (Jurnal Bakti Masyarakat Indonesia, 2025)
This community service activity aims to improve the efficiency, capacity, and product quality of the traditional herbal drink business "Sri Lestari," located in Tanjung Duren, Grogol, West Jakarta. This home-based enterprise has been producing herbal drinks from natural ingredients such as ginger, lemongrass, turmeric, and lemon, but it faces several challenges including manual production processes, low production capacity, inconsistent product quality, and poor hygiene. To address these issues, the community service team introduced two appropriate technologies (AT): an electrically powered slicing machine and a spinner machine for efficient extraction of herbal juice. The implementation method involved field observation, needs analysis, technical training, and hands-on guidance for the SME partners. The results showed significant improvements: production time was reduced from 3–4 hours to approximately 20 minutes per batch; production capacity doubled from 14–15 bottles to about 30 bottles per batch; and the consistency and cleanliness of the products increased. Additionally, the SME gained greater autonomy, having learned to operate and maintain the machines independently. In conclusion, the application of appropriate technology in this activity has effectively empowered the SME, enhanced the competitiveness of "Sri Lestari" traditional herbal products, and opened wider market opportunities, including entry into modern retail channels